S&T for ACP agriculture under Cotonou Agreement - Box, Louk de la Rive; Steinhauer, Nora; Ulmanen, Johanna (Technical Centre for Agricultural and Rural Cooperation, 2003)
Agriculture plays a central role in the economies of most ACP countries. Although agricultural innovations are likely to increase agricultural productivity, ACP governments have given low priority to investing in Science and Technology (S&T) for agriculture. In fact, investment in agricultural research and technology development appears to have steadily declined over the 1980s and 1990s, reflecting decreasing donor interest. One may therefore wonder to what extent investment in agricultural science and technology development is surviving as a global public good.